Pelayanan Pastoral Kedukaan Akibat Kematian Yang Mendadak - Amperiyana Nguru (Sekolah Tinggi Teologi SAPPI Ciranjang, 2019)
This research is intended to give attention to people who are grieving because of sudden death. Separation because of death is a